MEDIA RELATIONS PRACTICES IN SELECTED TERTIARY INSTITUTIONS IN TARABA STATE, NIGERIA - Gbaden, Chiakaan Jacob; Kente, Josiah Sabo; Adda, Lynn Danjuma (African Journal of Social and Behavioural Sciences, 2024)
This study examined media relations practices in selected tertiary institutions in Taraba State. The objectives of the study were to determine the extent to which media relations are practised by the selected tertiary institutions, identify the media relations approaches used by the institutions, and investigate the effectiveness of the approaches. The study adopted mixed methods research that included in-depth interviews and descriptive survey. The population of the study is 108, which comprises journalists, Vice Chancellors, Rectors, Registrars, and Information and Public Relations Officers from the selected tertiary institutions. Findings revealed that media relations is practised to significantly the selected tertiary institutions in Taraba State. Additionally, the study identified a variety of media relations approaches utilized by the institutions. These media relations strategies include the use of press conferences, prioritizing the willingness to answer questions, and sending invitations to events, among others. The study also found that challenges hindering the effectiveness of the media relations strategies adopted by the selected tertiary institutions include funding constraints, network connectivity issues, non-participation, and impromptu arrangements This study concludes that media relations play a vital role within tertiary institutions in Taraba State, highlighting their active engagement and diverse approaches. The study recommends, among others, that the government should provide more funding to the management of the institutions to enable them to carry out both their media relations and other activities more effectively.